The Heat Is On: A Mixed-Method Examination of Eating Behavior and Executive Functions Among Low Income Minority Girls During Summertime. (May 2019) - Egbert, Amy Heard; Bohnert, Amy M.; Bates, Carolyn R.; Loren, Dorothy M.; Creber, Chloe; Rosania, Kimberly A.; Ward, Amanda K.; Dugas, Lara R.; Silton, Rebecca L.
Despite evidence that youth gain weight disproportionately over the summer months, few studies examine contributing obesogenic behaviors. Utilizing a mixed-methods approach, this study examined associations between summertime dietary intake patterns and executive function among 79 low-income urban minority early adolescent girls (ages 9-13 years). Participants were interviewed via the multiple-pass 24-hour dietary recall method and completed individually administered executive function tasks. A subsample of 14 parents completed interviews to gather qualitative information about summertime eating patterns. Results suggested that participants consumed 25% to 35% more daily calories than recommended, and inhibition difficulties were associated with higher calorie and sugar-sweetened soft drink intake. In addition, over one third of participants were classified as nighttime eaters, and these participants had more difficulty with inhibition, even when accounting for sleep influences, and consumed more soft drinks than daytime eaters. Qualitative interviews consistently indicated that summertime changes food consumption as well as the timing and structure of the meals.